Growth Response of Robusta Coffee (Coffea canephora L.) Seedlings to Exogenous Salicylic Acid Application - Novie Pranata; Fakhrusy Zakariyya (Indonesian Coffee and Cocoa Research Institute, 2021)
To accelerate growth performance of Robusta coffee (Coffea canephora) seedling could be conducted through the application of exogenous plant hormone.Salicylic acid is one of plant hormones that widely applied to increase the plant growth for several plants, however, for coffee was still relative limited. This studywas aimed to determine the effect of salicylic acid on the growth of Robusta coffee seedlings which research was conducted at Indonesian Coffee and CocoaResearch Institute (ICCRI), Jember, East Java. This experiment was set using split plot design with three replications. The main plot was clones, which were BP 308and Sintaro clones. The seedlings were propagated from rooted cuttings. The subplot was the concentration of exogenous salicylic acid, that were control,0.6 mM, 1.2 mM, and 1.8 mM. The result demonstrated that BP 308 clone had higher rooting performance than Sintaro clone that shown by the higher rootvolume, root dry mass, and root/shoot ratio. In general, the application of salicylic acid could enhance the growth of Robusta coffee seedling. The application of 0.6 mMsalicylic acid increased plant growth of coffee seedlings. There was different response to concentration of application salicylic acid for both clones. The application of 0.6 mM salicylic acid could increase plant growth of BP 308, includeplant height, leaf area, stem dry mass, leaf dry mass, root/shoot ratio and total dry mass. Meanwhile, on Sintaro clone, application of 1.2 mM salicylic acid couldincrease leaf area, stem, leaf and total dry mass. The application of salicylic acid more than 1.2 mM led to detrimental effect of coffee seedlings.